2022
DOI: 10.1002/ptr.7473
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of commercial herbal dietary supplements used for dyslipidemia—Sales data and suspected adverse reactions

Abstract: Herbal dietary supplements (HDS) used for dyslipidemia represent a category of concern in Italy for suspected adverse reactions (ARs). However, we cannot estimate their safety, as we do not know their commercial profile. Sales data of HDS, and particularly, those used for dyslipidemia, were monitored for 2 years in two pharmacies of Rome. Meanwhile, spontaneous reports of suspected ARs potentially related to dyslipidemia supplements were collected by the Italian Phytovigilance System. The 50% of the total diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Drug-induced rhabdomyolysis is well described, especially among the statin medication class [1][2][3]. Rhabdomyolysis contributed to by herbal supplementation, including but not limited to licorice, red yeast rice, and jimson weed, is less well described, but there are reports found in the literature [4,5]. An area where there remains a paucity of research involves drug interactions between the statin medication class and herbal supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced rhabdomyolysis is well described, especially among the statin medication class [1][2][3]. Rhabdomyolysis contributed to by herbal supplementation, including but not limited to licorice, red yeast rice, and jimson weed, is less well described, but there are reports found in the literature [4,5]. An area where there remains a paucity of research involves drug interactions between the statin medication class and herbal supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the drugs most likely to cause rhabdomyolysis include psychiatric agents, antihistamines, illicit substances, and those affecting the cytochrome P450 system, such as statins ( Sauret et al, 2002 ; Hohenegger, 2012 ). In addition, concomitant use of Chinese herbal medicine and herbal dietary supplements (HDS) has been shown to be associated with rhabdomyolysis based on case reports and spontaneous reports of suspected adverse events ( Li et al, 2020 ; Allkanjari et al, 2022 ). Dipeptidyl peptidase (DPP)-4 inhibitors, one of the safest oral hypoglycemic agents that reduce the degradation of GLP-1, are usually not considered to cause rhabdomyolysis ( Mulvihill and Drucker, 2014 ; Marx et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%